Upaya Meminimalisir Konflik Perekrutan Badan Adhoc Pemilu 2024 : Studi Kasus Komisi Pemilihan Umum (KPU) Kabupaten Jombang - Firda Amalia; Nieke Rudyanty Winanda (Jurnal Ilmu Sosial dan Ilmu Politik)
General elections are a democratic process to directly elect representatives of the people. The process of organizing simultaneous elections will be held again in 2024. The potential for conflict will always accompany every stage of the election implementation. Both internal conflicts and external conflicts. For example, in the General Election Commission (KPU) of Jombang Regency, the conflict that arose was related to the problem of the recruitment system for the 2024 election adhoc body claimed to lack integrity. The purpose of this study is to describe the conflict in the recruitment of adhoc bodies as well as the efforts of the General Election Commission (KPU) of Jombang Regency in minimizing it. The research method uses descriptive qualitative with data collection techniques through document studies and in-depth interviews. The results of the research show that the potential for conflict in the recruitment of adhoc bodies is triggered by public disappointment so that they consider this institution to lack integrity, while efforts to minimize it include providing concrete data transparency.